Towards understanding the processes that govern variability in the Southern Hemisphere - Woodworth, Jonathan D., author; Thompson, David, advisor; Birner, Thomas, committee member; Yalin, Azer, committee member (Colorado State University. Libraries, 2013)
The climate at extratropical latitudes is strongly a result of the behavior of the zonal mean zonal wind and its inherent variability. This variability is dominated largely by the north-south fluctuation of the midlatitude jet and is identified in the Southern Hemisphere as the Southern Annular Mode (SAM). Recent observations have shown a tendency of the jet to move poleward due to, in part, the forcing associated with stratospheric cooling due to ozone loss and the tropical tropospheric warming from increasing greenhouse gases. Two dominant processes drive variability in the midlatitude jet: anomalies in the eddy momentum flux (EMF) and the eddy heat flux (EHF). In an attempt to link these processes, this study aims to diagnose a relationship in the observational data via two aspects: 1) To assess the extent to which feedbacks between the EMF and EHF give rise to the annular modes; and 2) To understand, in the context of the atmospheric energy cycle, the dominant patterns of variability of the EMF and EHF fields. Preliminary results reveal that the variability observed in the extratropical flow may exhibit a slight feedback between these processes. Additionally, it has been found that this variability may be viewed in the context of two distinct structures: (i) those that owe their existence to conversions between zonal-mean and eddy kinetic energy and (ii) those that owe their existence to conversions between zonal-mean and eddy potential energy. Past studies have largely focused on the former's impact on the extratropical circulation. However, not much emphasis has been placed on the latter, despite arguably playing an equally important role in driving the variability.
Keywords: feedback; midlatitude jet; mode; SAM; variability; zonal